1999
DOI: 10.1073/pnas.96.20.11664
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of NOZZLE , a gene involved in pattern formation and early sporogenesis during sex organ development in Arabidopsis thaliana

Abstract: Sexual reproduction is a salient aspect of plants, and elaborate structures, such as the f lowers of angiosperms, have evolved that aid in this process. Within the f lower the corresponding sex organs, the anther and the ovule, form the male and female sporangia, the pollen sac and the nucellus, respectively. However, despite their central role for sexual reproduction little is known about the mechanisms that control the establishment of these important structures. Here we present the identification and molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
331
1
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(347 citation statements)
references
References 29 publications
10
331
1
5
Order By: Relevance
“…Strains, Plant Growth, and Genotyping ap3-3 (Jack et al, 1992), nzz-1 (Schiefthaler et al, 1999), and ms1-1 (van der Veen and Wirtz, 1968) mutants, as well as wild-type plants of accession Landsberg erecta, were grown on a soil:vermiculite:perlite mixture under constant illumination at 20°C. T-DNA insertion lines (Supplemental Table S5; Alonso et al, 2003) for selected genes identified in this study were obtained from the Arabidopsis Biological Resource Center (Ohio State University).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Strains, Plant Growth, and Genotyping ap3-3 (Jack et al, 1992), nzz-1 (Schiefthaler et al, 1999), and ms1-1 (van der Veen and Wirtz, 1968) mutants, as well as wild-type plants of accession Landsberg erecta, were grown on a soil:vermiculite:perlite mixture under constant illumination at 20°C. T-DNA insertion lines (Supplemental Table S5; Alonso et al, 2003) for selected genes identified in this study were obtained from the Arabidopsis Biological Resource Center (Ohio State University).…”
Section: Methodsmentioning
confidence: 99%
“…In spl/nzz mutants, the nucellus and the pollen sac fail to form, indicating that SPL/NZZ, which encodes a putative transcription factor, plays a key role in the development of both male and female sporangia (Schiefthaler et al, 1999;Yang et al, 1999). ms1 mutants do not produce viable pollen but are otherwise phenotypically normal (Wilson et al, 2001;Ito and Shinozaki, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Arabidopsis, SPOROCYTELESS (SPL) and EXCESS MICROSPOROCYTE1 (EMS1) are two important genes regulating microsporogenesis (Schiefthaler et al, 1999;Yang et al, 1999;Zhao et al, 2002). In an effort to identify new genes for anther and pollen development, we compared gene expression profiles between wildtype and spl and ems1 mutant anthers (Wijeratne et al, 2007).…”
Section: The Cdm1 Gene Expression Patternmentioning
confidence: 99%
“…The specification of the sporocytes represents a critical step in the process of sporogenesis. The SPOROCYTE-LESS/NOZZLE (SPL/NZZ) gene which encodes a nuclear protein was identified as a key regulator of this stage of sporogenesis in Arabdiopsis [1,2]. In spl/nzz mutants, development of both male and female reproductive organs proceeds normally until the ACs are formed, but the ACs fail to differentiate into sporocytes.…”
mentioning
confidence: 99%